MEASURES TO PREVENT INFECTIOUS DISEASES - Mahammadiyeva Sevara Khidirboyevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Infectious diseases, that is, infectious diseases, are one of the issues of constant importance in the history of mankind. They are caused by bacteria, viruses, parasites, or fungi and are often transmitted from person to person, animal to person, or environment to person. Infectious diseases kill millions of people worldwide, and their spread is one of the major global health problems. Therefore, measures to prevent infectious diseases are very important for every society. This article discusses the main measures that should be taken to prevent infectious diseases and their importance.